Effect of kinematic variables on performance in women during a cross-country ski race - Rundell, K. W.; McCarthy, J. R. (Medicine & Science in Sports & Exercise, 1996)
The purpose of this study was to investigate the relationship of uphill cycle velocity, cycle length, and cycle rate in top U.S. female skiers during a multiple lap cross-country ski skating race. Eighteen female cross-country skiers served as subjects at the United States Women's 10-km Freestyle 1995 National Championships. The course consisted of two laps of the same 5-km loop. The selected filming section was an 11-12% uphill grade approximately 400 m long located at the 2.5- and 7.5-km mark. The video sector was approximately 12 m long at the conclusion of the climb. During the climb, the skating technique used by all skiers was the V-1. The results demonstrated that cycle length is positively related to cycle velocity during uphill ski skating and ultimately translates to faster race times by female cross-country ski racers. Lap 2 cycle velocity and cycle length demonstrated the strongest relationship to lap time and total race time. Moreover, cycle rate was not related to cycle velocity or lap race times and was not different between successful and less successful skiers. The slower climbing velocity noted during the latter half of the 10-km race was a consequence of a decreased cycle length and not cycle rate. This suggests that the degree of physical conditioning could be a factor in the ability to maintain cycle length and thus uphill cycle velocity.